Analisis pengaruh display, signage dan in-storeMedia terhadap perilaku pembelian konsumenDi luwes kartasura - Retnoningrum, Anggraeni; , Basworo Dibyo, S.E, M.Si (2016)
The purpose of this study is to determine the effect of Display, Signage and In-store Media on consumer buying behavior in Luwes Kartasura. The type of research is a quantitative research, which population taken from consumers with age above 17 years old who visit and shop at Luwes Kartasura, taken as many as 100 people. The sampling using purpossive sampling technique that is sampling with certain criteria. The technique of data collection through a questionnaire with Likert scale. Based on Regression Linier Analysis knowed that the constanta's value is positive 0,495. It shows if no situation of independent variables Display, Signage and In-Store Media the consumer buying behavior will staying high. Based on the results of t-test that variable Display acquired T-count is bigger than the table (2.080 > 1.985), variable Signage acquired T-count is bigger than the table (4.634 > 1.985), In-Store Media acquired T-count is bigger than the table (2.366 > 1.985) so it shows positive and significant influence on cunsumer buying behavior. The results of f-test obtained f-count is bigger than f-table (38.168 > 2.76), than Ho is rejected, it means Display variable (X1), Signage variable (X2) and In-Store Media variable (X3) influence on consumer buying behavior (Y) and based on the result of the test determination coefficient obtained R Square 0.544. It means the variation of variable change consumer buying behavior can be explain by Display variable (X1), Signage variable (X2) and In- Store Media variable (X3) by 54,4%. While the remaining 45,6% is explain by other variables outside the model.